DETERMINATION OF COAL PILLAR STABILITY PROBABILITY EQUATIONS USING THE BINARY LOGISTICS REGRESSION METHOD - Dwi Farras, M.
In the underground mining method, pillars are an important component to support the rock above the mine so it doesn't collapse. However, there are not a few cases of pillars that collapse even though they have a safety factor greater than one. Therefore, it is necessary to develop a probability equation for the stability of coal pillars in order to design coal pillars that have a high chance of being stable based on historical data on coal pillars that have been made. The probability equation for the stability of the coal pillars can be obtained using the binary logistic regression method based on the ratio of the width and height of the pillars and the safety factor of the pillars. Statistical processing of pillar data is carried out using software SPSS 26.0 to obtain the logistic regression coefficient so that the probability equation for the stability of the coal pillar can be formed. In the results of this study, the probability equation for the stability of a coal pillar is obtained which has three logistic regression coefficients, namely -6.323 (????0), - 0.227 (????1), and 8.147 (????2) and obtained the probability of stability of the coal pillar at stable pillar by 40.2%-100% and at failed pillar of 2.58% -88.84%. The minimum probability limit that a coal pillar must have is 90% to ensure stability.